Perempuan dan Media Massa - Nur, Iffatin (Sunan Kalijaga State Islamic University & The Asia Foundation, 2007)
The role of mass media is not only providing information to the public to fulfill their 'right to know' and 'right to expression', but also leading the creation of societies' images, myths, behavior, knowledge, even ideologies. Mass media produce new realities through texts, define facts or reality which amongst the semiotics such process is called creating the second reality from the first reality by the media. The media have created new realities in which men are portrayed as superior and engaging in all public spheres, whereas women are visualized as the weak. The production of mass media is also closely related to capitalist system of economy, which sometimes requires certain to become the victims; and women have been the victims in this capitalist system.